2020
DOI: 10.1186/s12876-020-01238-7
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile polyposis syndrome might be misdiagnosed as familial adenomatous polyposis: a case report and literature review

Abstract: Background Juvenile polyposis syndrome (JPS) is a rare disorder characterized by the presence of multiple juvenile polyps in the gastrointestinal tract, and germline mutations in SMAD4 or BMPR1A. Due to its rarity and complex clinical manifestation, misdiagnosis often occurs in clinical practice. Case presentation A 42-year-old man with multiple pedunculated colorectal polyps and concomitant rectal adenocarcinoma was admitted to our hospital. His mother had died of colon cancer. He was diagnosed with familial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
11
0
4
Order By: Relevance
“…[9] Furthermore, JPS can be diagnosed only in the absence of other hamartomatous polyposis syndromes, including PJS what excludes our patient as a JPS patient. [10] Polyps of juvenile type are mostly detected in childhood but are very rare in adulthood. [11] Thus, juvenile polyps may often be misdiagnosed as inflammatory polyps.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Furthermore, JPS can be diagnosed only in the absence of other hamartomatous polyposis syndromes, including PJS what excludes our patient as a JPS patient. [10] Polyps of juvenile type are mostly detected in childhood but are very rare in adulthood. [11] Thus, juvenile polyps may often be misdiagnosed as inflammatory polyps.…”
Section: Discussionmentioning
confidence: 99%
“…O'Riordan et al ( 13 ) found that ∼7%–14% of JPS polyps harbored adenomatous changes; however, adenomas as the sole histology of multiple colorectal polyps were not mentioned in any of these patients. Gao et al ( 8 ) reported a family with the BMPR1A variant and multiple juvenile polyps misdiagnosed as multiple adenomas. In our study, polyp histology in all 8 patients, initially reported to be adenomas, was revised by GI pathologists, and the diagnosis of adenoma was confirmed in all cases.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Therefore, endoscopy studies could help to differentiate FAP (familial adenomatous polyposis) from JPS, as in FAP, most polys have been noted to be sessile. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Elitsar et al, a review of patients with JPS revealed that 90.5% were stalked and only 9.5% were sessile 14 . Therefore, endoscopy studies could help to differentiate FAP (familial adenomatous polyposis) from JPS, as in FAP, most polys have been noted to be sessile 15 …”
Section: Discussionmentioning
confidence: 99%